Genome wide mapping of ETV6 binding sites in pre-B leukemic cells. Issue 1 (December 2018) - Neveu, Benjamin; Caron, Maxime; Lagacé, Karine; Richer, Chantal; Sinnett, Daniel
Abstract Genetic alterations in the transcriptional repressorETV6 are associated with hematological malignancies. Notably, the t(12;21) translocation leading to anETV6 -AML1 fusion gene is the most common genetic alteration found in childhood acute lymphoblastic leukemia. Moreover, most of these patients also lackETV6 expression, suggesting a tumor suppressor function. To gain insights onETV6 DNA-binding specificity and genome wide transcriptional regulation capacities, we performed chromatin immunoprecipitation experiments coupled to deep sequencing in a t(12;21)-positive pre-B leukemic cell line. This strategy led to the identification ofETV6 -bound regions that were further associated to gene expression.ETV6 binding is mostly cell type-specific as only few regions are shared with other blood cell subtypes. Peaks localization and motif enrichment analyses revealed that this unique binding profile could be associated with theETV6 -AML1 fusion protein specific to the t(12;21) background. This study underscores the complexity ofETV6 binding and uncoversETV6 transcriptional network in pre-B leukemia cells bearing the recurrent t(12;21) translocation.